IMPACT OF EMPLOYEES’ RETIREMENT PLANNING ON RETIREES’ ADJUSTMENT IN ABIA STATE MINISTRY OF EDUCATION (2014 – 2024) - Ejim, Onyebuchi O.; Umeh, Chijioke Sunday (African Journal of Social and Behavioural Sciences, 2025)
This study examined the impact of employees’ retirement planning on retirees’ adjustment in the Abia State Ministry of Education. The objectives are to determine ways in which employees’ retirement planning education, self-development, and investment affect the retirees’ adjustment in the state. Survey research design was adopted for the study. The population of the study consisted of the 3 educational zones in the state - Aba, Ohafia, and Umuahia- with a population size of 3,503 serving personnel and 3,024 retirees from the ministry. Using the Taro Yamane formula, a sample size of 377 respondents was randomly selected from a population of 6,527 individuals. The respondents were randomly selected through a stratified technique in the three zones on the basis of 4 local government areas for a zone. A questionnaire titled Employees’ Retirement Planning and Retirees’ Adjustment Survey Questionnaire (ERPRSQ), structured in a Likert format, was administered for data collection, complemented with interviews and secondary data. The data collected were analyzed using frequency counts, percentages, and means. The study was anchored on the Expectancy Theory. The hypotheses were tested using Pearson Product Moment Correlation Coefficient Statistics. It was discovered that lack of employees’ retirement planning education, poor self-development, and business investment negatively affected the retirees’ adjustment in the state. It was recommended that the government/ministry of education should regularly organize workshops/seminars to educate the employees on the need to adopt effective retirement planning education and good self-development programmes, as well as initiate business ventures while in the service to guarantee effective retirees’ adjustment in the state.